2020
DOI: 10.1590/1982-7849rac2020200047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Budgetary Participation on Managerial Attitudes, Satisfaction, and Managerial Performance

Abstract: Objective: the purpose of this paper is to investigate the effects of budget participation on management attitudes, job satisfaction, and managerial performance of controllers of Brazilian companies. Methodology: a descriptive, survey, and quantitative research was conducted from a sample of 316 individuals with budgetary responsibility. Results: the results indicated that budgetary participation directly and positively influences managerial attitudes toward budgeting, job satisfaction, and controllers’ perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
1
6
0
5
Order By: Relevance
“…This variable was measured using 6 question items adopted from the study (Dunk, 1993); 2) Budget participation is a concept used to describe the extent to which subordinates are allowed to choose their programs in action (Milani, 1975). Indicators regarding budget participation are participation in budget preparation, the influence of budget targeting, and the influence of opinions given (Kenis, 1979). This variable was measured using five questions, which were adopted from Kenis's (1979) study; 3) Organizational culture is a culture formed as a result of a collective agreement that will make members of the organization have a sense of responsibility in implementing essential aspects of the organizational culture (Agusti, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This variable was measured using 6 question items adopted from the study (Dunk, 1993); 2) Budget participation is a concept used to describe the extent to which subordinates are allowed to choose their programs in action (Milani, 1975). Indicators regarding budget participation are participation in budget preparation, the influence of budget targeting, and the influence of opinions given (Kenis, 1979). This variable was measured using five questions, which were adopted from Kenis's (1979) study; 3) Organizational culture is a culture formed as a result of a collective agreement that will make members of the organization have a sense of responsibility in implementing essential aspects of the organizational culture (Agusti, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Indicators regarding budget participation are participation in budget preparation, the influence of budget targeting, and the influence of opinions given (Kenis, 1979). This variable was measured using five questions, which were adopted from Kenis's (1979) study; 3) Organizational culture is a culture formed as a result of a collective agreement that will make members of the organization have a sense of responsibility in implementing essential aspects of the organizational culture (Agusti, 2012). Indicators regarding this corporate culture are involvement, adaptation, consistency, and mission (Robbins, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…A budget system that allows managers to participate and be responsible for the process of preparing the budget and setting goals can be positive for the organization. The literature highlights among the positive effects: increase in positive attitudes and increased performance at work (Argyris, 1952;Jacomossi et al, 2018;Lunardi et al, 2020;Mia, 1988;Nouri & Parker, 1998), information sharing (Kyj & Parker, 2008;Lunardi et al, 2020;Shields & Shields, 1998), employee satisfaction (Chong et al, 2005;Kyj & Parker, 2008;Zonatto, Nascimento, Lunardi, & Degenhart, 2020), perception of organizational justice (Derfuss, 2009;Kyj & Parker, 2008;Sholihin, Pike, Mangena, & Li, 2011;Wentzel, 2002), open communication and interaction with the employee (Lavarda & Almeida, 2013), motivation (Kyj & Parker, 2008), and definition of budget goals (Hassel & Cunningham, 1996;Maiga, 2005;Milani, 1975).…”
Section: Budget Participationmentioning
confidence: 99%
“…The latest studies on the relationship between budget and job satisfaction, among others, were conducted by Farahmita (2016), Sim and Utami (2018), Zonatto et al (2020), andFarahmita (2016) revealed that budgetary participation and job satisfaction have an interaction effect on performance. Sim and Utami (2018) found evidence that budgetary participation affects job satisfaction with job relevant information as the mediating variable.…”
Section: Budgeting and Job Satisfactionmentioning
confidence: 99%
“…Sim and Utami (2018) found evidence that budgetary participation affects job satisfaction with job relevant information as the mediating variable. Meanwhile, Zonatto et al (2020) found that budgetary participation affects the job satisfaction.…”
Section: Budgeting and Job Satisfactionmentioning
confidence: 99%